Enhancing crops production based on environmental status using machine learning techniques - Talukder, Shiyam; Jannat, Habiba; Saha, Sukanta; Sengupta, Katha (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.